An evaluation of pharmacists' expectations towards pharmacogenomics. (January 2013) - de Denus, Simon; Letarte, Nathalie; Hurlimann, Thierry; Lambert, Jean-Philippe; Lavoie, Annie; Robb, Laura; Sheehan, Nancy L; Turgeon, Jacques; Vadnais, Barbara
Background: Given their expertise in pharmacotherapy, pharmacists are well positioned to play a leading role in the implementation of pharmacogenomics in clinical practice. However, little is known about the opinions of pharmacists towards pharmacogenomics or their willingness to integrate this new field in their practice.Methods: We conducted a survey of 284 pharmacists practicing in the province of Québec (Canada) to describe the opinions, expectations and concerns of pharmacists toward pharmacogenomics.Results: Pharmacists were very hopeful regarding the potential role of pharmacogenomics. Moreover, more than 95% of responders would be willing to recommend pharmacogenomic testing. Nevertheless, only 7.7% of pharmacists currently felt comfortable advising patients based on pharmacogenomic test results. Accordingly, the majority of responders (96.6%) indicated that they would like to undertake continuing education related to pharmacogenomics.Conclusion: Pharmacists are extremely hopeful towards pharmacogenomic testing. Furthermore, a vast majority is willing to integrate these tests as part of their clinical practice. Proper education will be required if the integration of pharmacogenomics in patient care is to be optimal. Original submitted 21 September 2012; Revision submitted 16 November 2012